An Analysis of Performance Variability in AWS Virtual Machines - Lima, Miguel de; Teylo, Luan; Drummond, Lúcia (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2024: Anais do XXV Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/sscad.2024.244526, 2024)
Cloud computing platforms are essential for a wide range of applications, including High-Performance Computing (HPC) and artificial intelligence. However, the performance variability of virtual machines (VMs) in these shared environments presents significant challenges. This paper provides an extensive month-long analysis of the performance variability of C family VMs on Amazon Web Services (AWS) across two regions (us-east-1 and sa-east-1), various instance generations, and market types. Our findings indicate that Graviton processors (c6g.12xlarge and c7g.12xlarge) exhibit minimal performance variability and high cost-effectiveness, with the c7g.12xlarge instance, in particular, offering significantly reduced execution times and lower costs. Intel and AMD instances, while showing performance improvements from generation c6 to c7, exhibited up to 20% variability.